Health-related quality of life in older women with injuries: a nationwide study - Kwak, Yeunhee; Ahn, Jung-Won (Frontiers in Public Health, 2023)
This study aims to describe the health-related quality of life (HRQoL) and influencing factors of older women who experienced injuries. This study is a secondary analysis of data from 4,217 women aged 65 years or older sampled from the Korea National Health and Nutrition Examination Survey (KNHANES) (2016-2020) database. Two-way analysis of variance was used to analyze the data. The mean HRQoL scores of older women with and without injuries were 0.81 ± 0.19 (n = 328) and 0.85 ± 0.17 (n = 3,889), respectively, which were significantly different (p < .001). The results of multiple regression analysis revealed that working, physical activity, BMI, osteoarthritis, stress, and subjective health status significantly affected the HRQoL of older women with injuries, and the explanatory power of the model was 29%. The results of this study on factors affecting HRQoL can contribute to the understanding of the experience of older women with injuries and can be used as a reference to develop health promotion programs.